FROM INSECURE ATTACHMENT TO SOCIAL RECONNECTION: DENVER’S HEALING JOURNEY IN TONI MORRISON’S BELOVED - Dhea Tri Arvinta; Prayudias Margawati (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2026)
This article examines how a second-generation daughter character takes a psychological path toward healing the historical trauma she inherited and the severe sense of emotional detachment in a fragmented household. Even though the tragic past of the maternal figure is usually the center of the literature analysis, this work will attempt to alter the interpretive lens toward the dynamics of a daughter overcoming her psychological paralysis. Applying a qualitative literary-critical design, the proposed study will employ a dual-theoretical model of attachment theory and trauma theory to examine the latent narrative nuances. It was done through systematic close reading of particular narrative units, which collected the data based on aspects of spatial symbolism, internal monologues, and the dynamics between characters. The findings reveal two main mechanisms in the character’s storyline. First, her excessive domestic seclusion and psychosomatic withdrawal, namely, two years of deafness and a physical retreat into a secluded natural setting, are diagnosed as the direct result of a broken maternal attachment and deep, insecure attachment. The haunted-house setting is essentially unhelpful as a secure base; it is an inhospitable refuge that reinforces her isolation. Second, the daughter character's definitive recovery is achieved not through internal resilience alone but through an active process of social reconnection. She establishes reparative interpersonal relationships with substitute maternal figures by breaking the spatial boundaries of her isolation and ultimately mobilizing a collective intervention, which allows her to overcome her psychological barriers. The study concludes that resolving intergenerational trauma requires rebuilding social connections to deliberately break entrenched insecure attachment patterns. These findings contribute to Morrison scholarship by demonstrating Denver's agency and offering a replicable dual-theory framework for analyzing trauma recovery in literary texts.